The SAGE dictionary of cultural studies - Barker, Chris (SAGE, 2004)
This dictionary makes a major contribution to cultural studies both defining the field and providing the key concepts. It provides over 250 entries on concepts and 50 on key theorists.
Keywords: Culture : Study and teaching : Dictionaries; Culture : Study and teaching : Dictionaries